Influence of interface morphology on hysteresis in vapor-deposited perovskite solar cells - Patel, J; Wong-Leung, J; Van Reenen, S; Sakai, N; Wang, J; Parrott, E; Liu, M; Snaith, H; Herz, L; Johnston, M (Wiley, 2016)
Hysteresis in the current–voltage characteristics of vapor-deposited perovskite solar cells is shown to originate from an amorphous region of CH3NH3PbI3 at the interface with the device's electron transport layer. Interface engineering is used to produce highly crystalline perovskite material at this interface which results in hysteresis-free evaporated planar heterojunction solar cells.